STUDY OF PHENOLCARBONIC ACIDS OF SALIX TRIANDRA L. TENDRILS GROWING IN THE NORTH CAUCASUS - E. G. Sannikova; O. I. Popova; E. V. Kompantseva; O. O. Frolova (Фармация и фармакология (Пятигорск))
Qualitative and quantitative composition of phenolcarbonic acids in one year tendrils of Salix triandra L. was determined. Identification in quantitative determination of certain phenolcarbonic acids was carried out using high-performance liquid chromatography. Six individual substances were discovered. The total content of the sum of phenolcarbonic acids was determined with extractionphotometric method, based on a selective extraction from acidulous solution into ethyl acetate. The highest content of phenolcarbonic acids (about 0.47%) was detected in the leaves of Salix triandra L., the lowest content was detected in the tendrils without leaves (about 0.40%). Phenolcarbonic acids discovered in the tendrils of Salix triandra L. may significantly contribute to the total pharmacological effect.